2014
DOI: 10.1111/jne.12207
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of the Genes Encoding RFAmide‐Related Peptide‐3, the Human Orthologue of Gonadotrophin‐Inhibitory Hormone, and its Receptor (GPR147) in Patients with Gonadotrophin‐Releasing Hormone‐Dependent Pubertal Disorders

Abstract: RFamide-related peptide-3 (RFRP-3), the orthologue of avian gonadotrophin-inhibitory hormone, and its receptor GPR147 have been recently identified in the human hypothalamus, and their roles in the regulation of reproductive axis has been studied. The present study aimed to investigate whether the presence of variants in the genes encoding human RFRP-3 (NPVF gene) and its receptor, GPR147 (NPFFR1 gene), is associated with the occurrence of gonadotrophin-releasing hormone-dependent pubertal disorders. Seventy-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
(57 reference statements)
0
16
0
1
Order By: Relevance
“…Pubertal analyses of null mice evidenced that GPR147 KO males, but not females, displayed constitutively elevated LH levels before and during puberty, whereas pubertal progression was not apparently altered by the congenital lack of GPR147 in either sex [35]. In accordance with this suggestion, a human genetics study revealed that the presence of variants in the genes encoding RFRP-3 and GPR147 is not associated with the occurrence of GnRH-pubertal disorders [34]. However, a 2015 study, by Semaan and Kauffman, showed a decrease in RFRP-3 expression in the hypothalamic dorsomedial nucleus during the prepubertal stage in mice [37].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Pubertal analyses of null mice evidenced that GPR147 KO males, but not females, displayed constitutively elevated LH levels before and during puberty, whereas pubertal progression was not apparently altered by the congenital lack of GPR147 in either sex [35]. In accordance with this suggestion, a human genetics study revealed that the presence of variants in the genes encoding RFRP-3 and GPR147 is not associated with the occurrence of GnRH-pubertal disorders [34]. However, a 2015 study, by Semaan and Kauffman, showed a decrease in RFRP-3 expression in the hypothalamic dorsomedial nucleus during the prepubertal stage in mice [37].…”
Section: Discussionmentioning
confidence: 96%
“…Our data show that ICV injection of RFRP-3 significantly delay the timing of puberty onset, characterized by delayed vaginal opening time and uterine development; it also reduce the serum levels of LH and E2. Recently, several findings suggested that endogenous RFRP-3 signaling may not be necessary for the timing of puberty [34, 35]. Pubertal analyses of null mice evidenced that GPR147 KO males, but not females, displayed constitutively elevated LH levels before and during puberty, whereas pubertal progression was not apparently altered by the congenital lack of GPR147 in either sex [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This three-nucleotide in frame deletion resulted in the absence of the isoleucine at position 71, adjacent to lysine at an endoproteolytic cleavage site of GnIH precursor polypeptide (Ubuka et al, 2009c). This deletion of the isoleucine at position 71 was associated with a lower risk of CPP, and the two men with nIHH were both homozygotes for this variant (Lima et al, 2014).…”
Section: Polymorphisms In Gnih Precursor Genementioning
confidence: 93%
“…There were significant associations between polymorphic loci and age at first egg, body weight at first egg and egg production in 300 days (Hu et al, 2015). Lima et al (2014) reported that there is a three-nucleotide in frame deletion in the human GnIH precursor gene (p.I71_K72), with a smaller proportion in the idiopathic central precocious puberty (CPP) (5%) compared to the normosmic isolated hypogonadotrophic hypogonadism (nIHH) (15%) group. This three-nucleotide in frame deletion resulted in the absence of the isoleucine at position 71, adjacent to lysine at an endoproteolytic cleavage site of GnIH precursor polypeptide (Ubuka et al, 2009c).…”
Section: Polymorphisms In Gnih Precursor Genementioning
confidence: 97%